Applying ‘case method’ in the teaching of basic medical sciences in a medical curriculum - Muhammad, Naznin; Abdullah, Nor Zamzila; Oothuman, Pakeer; Myint, Yi Yi (IIUM Medical Journal Malaysia, 2016)
Introduction: Case method (CM) as a teaching methodology to promote active learning of students has been successfully employed in a number of fields. In the Medical Programme of International Islamic University Malaysia (IIUM) we examined the application of CM in the teaching of basic medical sciences by integrating knowledge in these disciplines into the clinical sciences in a large group of students. Methods: This study involved Phase I preclinical medical students (Years 1 and 2). Thirteen CM modules were developed. A content-expert facilitator led a two-hour session for each of the modules which involved a class of about 130 students. Following such an implementation, the perception of students towards CM was studied through a self-administered questionnaire and focus group discussion. Results: More than 70% of these students agreed that CM sessions made efficient use of time. The structure promoted learning and helped develop problemsolving skills. CM sessions also provided opportunities for tutor participation and feedback. About 80% of Year 1 students and 60% of Year 2 students preferred to have both Problembased Learning and CM incorporated into the medical curriculum of IIUM. Findings of the focus group discussion are discussed. Conclusions: CM has a role in the teaching of the applied aspects of various disciplines of basic medical sciences.